Area-Dependent Resistive Switching and Interfacial Dynamics in GCMO-Based Memristors - Antola, Anni; Laaksonen, Johanna; Huhtinen, Hannu; Angervo, Ilari; Granroth, Sari; Schulman, Alejandro; Laukkanen, Pekka; Paturi, Petriina (AMER CHEMICAL SOC, 2025)
This study explores the area-dependent resistive switching (RS) characteristics of Gd0.2Ca0.8MnO3 (GCMO)-based memristors with aluminum (Al) and gold (Au) electrodes, emphasizing their potential for neuromorphic computing applications. Using a combination of electrical measurements and X-ray photoelectron spectroscopy (XPS), we demonstrate that the high-resistance (HRS) and low-resistance (LRS) states exhibit predictable scaling with device area, with HRS resistances ranging from 107 to 108 Omega and LRS from 105 to 107 Omega, supporting the hypothesis of interface-type RS. XPS depth profiling revealed notable differences in AlO x interfacial layer composition between HRS and LRS, with a higher oxide content and a widened interfacial region in HRS. Additionally, the multistate RS capability of up to ten distinct levels was achieved by modulating applied voltages, highlighting GCMO's suitability as a material for synaptic weight storage in artificial neural networks. Our findings underscore GCMO's promise for energy-efficient, scalable memristor-based systems.